2007
DOI: 10.1128/mcb.01550-06
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Osteoblast Differentiation by Selective Activation of Kinase-Mediated Actions of the Estrogen Receptor

Abstract: Estrogens control gene transcription by cis or trans interactions of the estrogen receptor (ER) with target DNA or via the activation of cytoplasmic kinases. We report that selective activation of kinase-mediated actions of the ER with 4-estren-3␣,17␤-diol (estren) or an estradiol-dendrimer conjugate, each a synthetic compound that stimulates kinase-mediated ER actions 1,000 to 10,000 times more potently than direct DNA interactions, induced osteoblastic differentiation in established cell lines of uncommitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 71 publications
3
51
0
1
Order By: Relevance
“…In contrast, 10 nM naringin could induce ERa phosphorylation at serine 118 in UMR-106 cells in a ligand-independent manner. Recent studies by Kousteni's group suggested that ligand, which activates kinase-mediated actions of ER, could reverse the loss of bone mass and strength in OVX mice without significant stimulatory effects on reproductive organs (Kousteni et al, 2002), and that kinase-mediated actions of the ER are important for inducing osteoblast differentiation (Kousteni et al, 2007). The fact that naringin could reverse bone loss in OVX mice without any uterotrophic effects suggests that it might induce osteoblast differentiation via kinase-mediated actions of the ER.…”
Section: Naringin and Anabolic Effects In Bone W-y Pang Et Almentioning
confidence: 99%
“…In contrast, 10 nM naringin could induce ERa phosphorylation at serine 118 in UMR-106 cells in a ligand-independent manner. Recent studies by Kousteni's group suggested that ligand, which activates kinase-mediated actions of ER, could reverse the loss of bone mass and strength in OVX mice without significant stimulatory effects on reproductive organs (Kousteni et al, 2002), and that kinase-mediated actions of the ER are important for inducing osteoblast differentiation (Kousteni et al, 2007). The fact that naringin could reverse bone loss in OVX mice without any uterotrophic effects suggests that it might induce osteoblast differentiation via kinase-mediated actions of the ER.…”
Section: Naringin and Anabolic Effects In Bone W-y Pang Et Almentioning
confidence: 99%
“…Estrogen has been shown to increase osteoclast apoptosis and inhibit their generation through a decreased ratio of receptor for RANKL to OPG [4][5][6][7]. The effects that estrogen exert on osteoblast proliferation and differentiation are less clear but its apoptosis-reducing effects on osteoblasts are well supported [8][9][10][11]. Hormone replacement therapy (HRT) has been shown to be efficacious in maintaining bone mass and reducing fracture risk in post-menopausal women [12,13].…”
Section: Introductionmentioning
confidence: 98%
“…This strongly suggests that ERRa regulation of WNT target genes is independent of b-catenin translocation. DNA-binding-independent activities through kinase interactions have been demonstrated for the estrogen receptor (ER) in osteoblast differentiation (Kousteni et al 2007). To test whether ERRa DNA binding was required for activation of the TCF reporter, we generated point mutants in the DNA-binding domain of ERRa.…”
Section: Activation Of Wnt Signaling By Erracpgc-1a Is Cell Intrinsicmentioning
confidence: 99%